Systemic barriers and untapped potentials: a SWOT study on the implementation of natural/small water retention measures in Europe - Julia Szulecka; Ingrid Nesheim; Federica Monaco; Anne-Grete Buseth Blankenberg; Veronika Čápová; Natalja Čerkasova; Jovita Mėžinė; Joana Eichenberger; Kinga Farkas-Iványi; Marie Anne Eurie Forio; Petr Fučík; Martyn N. Futter; et al. (Journal of Rural Studies, 2026)

Seasonal forecasting of dissolved organic carbon in a Mediterranean catchment: Enhancing upstream control of disinfection by-product precursors - Angela Pedregal-Montes; Daniel Mercado-Bettín; Martyn Futter; José L. J. Ledesma; Maria José Farré; Rafael Marcé; Eleanor Jennings (Environmental Monitoring and Assessment, 2026)
Increasing climatic aridity and growing anthropogenic pressures are expected to alter dissolved organic matter (DOM) dynamics in Mediterranean river basins, with implications for environmental monitoring and drinking water source management. Dissolved organic carbon (DOC), a bulk indicator of DOM and an operational surrogate for disinfection by-products (DBP) precursors, is routinely monitored at drinking water sources but remains difficult to anticipate on seasonal timescales. Here, we present a reproducible open-source workflow that extends conventional monitoring by integrating seasonal climate forecasts (SEAS5) with coupled hydrological and catchment carbon models to generate probabilistic monthly predictions of streamflow and DOC at the inflow of a Mediterranean drinking water reservoir. Seasonal hindcast evaluation using the Continuous Ranked Probability Skill Score (CRPSS) showed limited skill for meteorological variables beyond 1 month, while streamflow exhibited positive skill at short lead times across most seasons. Notably, DOC forecasts achieved the highest and most persistent skill, with CRPSS values exceeding 0.3 for winter initializations and lead times up to 4 months, consistent with catchment system memory. Forecast experiments successfully distinguished contrasting wet and dry hydroclimatic conditions, reproducing higher and more persistent DOC concentrations during the dry period. To support operational use, the forecasts were translated into a co-developed monthly report to provide early warning of periods with elevated organic matter levels in source waters. While DOC alone does not capture the full complexity of DBP formation, the workflow provides a transferable approach for seasonal assessment of source water organic matter dynamics in hydroclimatically variable, human-impacted catchments.

Estimating landscape-level water storage potential as a tool to mitigate floods and nutrient losses - Faruk Djodjic; Pia Geranmayeh; Emma E. Lannergård; Martyn Futter (Journal of Environmental Management, 2025)

Widespread and persistent oligotrophication of northern rivers - Jenny L. Nilsson; Sara Camiolo; Brian Huser; Oskar Agstam-Norlin; Martyn Futter (Science of The Total Environment, 2024)

Retention efficiency for microplastic in a landscape estimated from empirically validated dynamic model predictions - Magnus Norling; Rachel Hurley; Theresa Schell; Martyn N. Futter; Andreu Rico; Marco Vighi; Alberto Blanco; José L.J. Ledesma; Luca Nizzetto (Journal of Hazardous Materials, 2024)

Water quality in a large complex catchment: Significant effects of land use and soil type but limited ability to detect trends - Sara Sandström; Emma E. Lannergård; Martyn N. Futter; Faruk Djodjic (Journal of Environmental Management, 2024)

Publisher Correction: Leveraging research infrastructure co-location to evaluate constraints on terrestrial carbon cycling in northern European forests - Martyn N. Futter; Thomas Dirnböck; Martin Forsius; Jaana K. Bäck; Nathalie Cools; Eugenio Diaz-Pines; Jan Dick; Veronika Gaube; Lauren M. Gillespie; Lars Högbom; Hjalmar Laudon; Michael Mirtl; et al. (Ambio, 2023)

Quantification of the effect of environmental changes on the brownification of Lake Kukkia in southern Finland - Katri Rankinen; Virpi Junttila; Martyn Futter; José Enrique Cano Bernal; Daniel Butterfield; Maria Holmberg (Ambio, 2023)
The browning of surface waters due to the increased terrestrial loading of dissolved organic carbon is observed across the northern hemisphere. Brownification is often explained by changes in large-scale anthropogenic pressures (including acidification, and climate and land-use changes). We quantified the effect of environmental changes on the brownification of an important lake for birds, Kukkia in southern Finland. We studied the past trends of organic carbon loading from catchments based on observations taken since the 1990s. We created hindcasting scenarios for deposition, climate and land-use change in order to simulate their quantitative effect on brownification by using process-based models. Changes in forest cuttings were shown to be the primary reason for the brownification. According to the simulations, a decrease in deposition has resulted in a slightly lower leaching of total organic carbon (TOC). In addition, runoff and TOC leaching from terrestrial areas to the lake was smaller than it would have been without the observed increasing trend in temperature by 2 °C in 25 years.

Leveraging research infrastructure co-location to evaluate constraints on terrestrial carbon cycling in northern European forests - Martyn N. Futter; Thomas Dirnböck; Martin Forsius; Jaana K. Bäck; Nathalie Cools; Eugenio Diaz-Pines; Jan Dick; Veronika Gaube; Lauren M. Gillespie; Lars Högbom; Hjalmar Laudon; Michael Mirtl; et al. (Ambio, 2023)
Integrated long-term, in-situ observations are needed to document ongoing environmental change, to “ground-truth” remote sensing and model outputs and to predict future Earth system behaviour. The scientific and societal value of in-situ observations increases with site representativeness, temporal duration, number of parameters measured and comparability within and across sites. Research Infrastructures (RIs) can support harmonised, cross-site data collection, curation and publication. Integrating RI networks through site co-location and standardised observation methods can help answers three questions about the terrestrial carbon sink: (i) What are present and future carbon sequestration rates in northern European forests? (ii) How are these rates controlled? (iii) Why do the observed patterns exist? Here, we present a conceptual model for RI co-location and highlight potential insights into the terrestrial carbon sink achievable when long-term in-situ Earth observation sites participate in multiple RI networks (e.g., ICOS and eLTER). Finally, we offer recommendations to promote RI co-location.

Comparing effects of microplastic exposure, FPOM resource quality, and consumer density on the response of a freshwater particle feeder and associated ecosystem processes - Ze Hui Kong; Francis J. Burdon; Amélie Truchy; Mirco Bundschuh; Martyn N. Futter; Rachel Hurley; Brendan G. McKie (Aquatic Sciences, 2023)
Fine particulate organic matter (FPOM) is an important basal resource in stream ecosystems for deposit- and filter-feeding macroinvertebrates (collectively ‘particle feeders’). Microplastics (MP) share many characteristics with FPOM (e.g. size range, surface area to volume ratios) and are potentially consumed by particle feeders. Accordingly, MP contamination of natural FPOM pools might affect particle feeder growth and survival, particularly when background FPOM resource quality is low, or intraspecific competition is high. We conducted a microcosm experiment to evaluate how a realistic (1400 particles/kg sediment) polyethylene MP ( ø = 45–53 µm) concentration interacts with FPOM ( ø = 63–250 µm) resource quality (low versus high nutrient content) and consumer density (10 versus 20 individuals per microcosm) to affect growth and survival of larval Chironomus riparius (Diptera: Chironomidae), a model particle feeder. We additionally quantified community respiration, based on three hour measurements of oxygen consumption in the microcosms at the end of the experiment. MP exposure reduced larval body lengths by 26.7%, but only under the low consumer density treatment. MPs reduced community respiration by 26.2%, but only in the absence of chironomids, indicating an impact on microbial respiration. In comparison, low resource quality and high consumer density were associated with 53.5–70.2% reductions in community respiration, chironomid body length and/or body mass. These results suggest that effects of contamination of FPOM with MPs at environmentally realistic concentrations on the life histories of particle feeders such as C. riparius might be limited, especially relative to the effects of resource quality and consumer density. However, the reduction in microbial respiration when MPs were present highlights the need for further research addressing MP impacts on microbes, given their key roles in ecosystem functioning.

Spatial and temporal variability in summertime dissolved carbon dioxide and methane in temperate ponds and shallow lakes - Nicholas E. Ray; Meredith A. Holgerson; Mikkel Rene Andersen; Jānis Bikše; Lauren E. Bortolotti; Martyn Futter; Ilga Kokorīte; Alan Law; Cory McDonald; Jorrit P. Mesman; Mike Peacock; David C. Richardson; et al. (Limnology and Oceanography, 2023)
Small waterbodies have potentially high greenhouse gas emissions relative to their small footprint on the landscape, although there is high uncertainty in model estimates. Scaling their carbon dioxide (CO 2 ) and methane (CH 4 ) exchange with the atmosphere remains challenging due to an incomplete understanding and characterization of spatial and temporal variability in CO 2 and CH 4 . Here, we measured partial pressures of CO 2 ( p CO 2 ) and CH 4 ( p CH 4 ) across 30 ponds and shallow lakes during summer in temperate regions of Europe and North America. We sampled each waterbody in three locations at three times during the growing season, and tested which physical, chemical, and biological characteristics related to the means and variability of p CO 2 and p CH 4 in space and time. Summer means of p CO 2 and p CH 4 were inversely related to waterbody size and positively related to floating vegetative cover; p CO 2 was also positively related to dissolved phosphorus. Temporal variability in partial pressure in both gases weas greater than spatial variability. Although sampling on a single date was likely to misestimate mean seasonal p CO 2 by up to 26%, mean seasonal p CH 4 could be misestimated by up to 64.5%. Shallower systems displayed the most temporal variability in p CH 4 and waterbodies with more vegetation cover had lower temporal variability. Inland waters remain one of the most uncertain components of the global carbon budget; understanding spatial and temporal variability will ultimately help us to constrain our estimates and inform research priorities.

Influence of forest management changes and reuse of peat production areas on water quality in a northern river - Katri Rankinen; Martyn Futter; Joy Bhattacharjee; José E. Cano Bernal; Emma E. Lannergård; Maria Ojanen; Anna-Kaisa Ronkanen; Hannu Marttila; Seppo Hellsten (CATENA, 2023)

Three Decades of Changing Nutrient Stoichiometry from Source to Sea on the Swedish West Coast - Mike Peacock; Martyn N. Futter; Sara Jutterström; Dolly N. Kothawala; Filip Moldan; Johanna Stadmark; Chris D. Evans (Ecosystems, 2022)
European ecosystems have been subject to extensive shifts in anthropogenic disturbance, primarily through atmospheric deposition, climate change, and land management. These changes have altered the macronutrient composition of aquatic systems, with widespread increases in organic carbon (C), and declines in nitrogen (N) and phosphorus (P). Less well known is how these disturbances have affected nutrient stoichiometry, which may be a more useful metric to evaluate the health of aquatic ecosystems than individual nutrient concentrations. The Swedish west coast has historically experienced moderate to high levels of atmospheric deposition of sulfate and N, and eutrophication. In addition, coastal waters have been darkening with damaging effects on marine flora and fauna. Here, we present three decades of macronutrient data from twenty lakes and watercourses along the Swedish west coast, extending from headwaters to river mouths, across a range of land covers, and with catchments ranging 0.037–40,000 km 2 . We find a high degree of consistency between these diverse sites, with widespread increasing trends in organic C, and declines in inorganic N and total P. These trends in individual macronutrients translate into large stoichiometric changes, with a doubling in C:P, and increases in C:N and N:P by 50% and 30%, showing that freshwaters are moving further away from the Redfield Ratio, and becoming even more C rich, and depleted in N and P. Although recovery from atmospheric deposition is linked to some of these changes, land cover also appears to have an effect; lakes buffer against C increases, and decreases in inorganic N have been greatest under arable land cover. Our analysis also detects coherently declining P concentrations in small forest lakes; so called (and unexplained) “oligotrophication.” Taken together, our findings show that freshwater macronutrient concentrations and stoichiometry have undergone substantial shifts during the last three decades, and these shifts can potentially explain some of the detrimental changes that adjacent coastal ecosystems are undergoing. Our findings are relevant for all European and North American waters that have experienced historically high levels of atmospheric deposition, and provide a starting point for understanding and mitigating against the trajectories of long-term change in aquatic systems.

Microplastics in terrestrial ecosystems: Moving beyond the state of the art to minimize the risk of ecological surprise - Didier L. Baho; Mirco Bundschuh; Martyn N. Futter (Global Change Biology, 2021)
Microplastic (plastic particles measuring

Nordic Bioeconomy Pathways: Future narratives for assessment of water-related ecosystem services in agricultural and forest management - Jelena Rakovic; Martyn N. Futter; Katarina Kyllmar; Katri Rankinen; Marc I. Stutter; Jan Vermaat; Dennis Collentine (Ambio, 2020)
Further development of the bioeconomy, the substitution of bioresources for fossil resources, will lead to an increased pressure on land and water resources in both agriculture and forestry. It is important to study whether resultant changes in land management may in turn lead to impairment of water services. This paper describes the Nordic Bioeconomy Pathways (NBPs), a set of regional sectoral storylines nested within the global Shared Socioeconomic Pathways (SSP) framework developed to provide the BIOWATER research program with land management scenarios for projecting future developments to explore possible conflicts between land management changes and the Water Framework Directive (WFD). The NBPs are a set of narrative storylines capturing a range of plausible future trajectories for the Nordic bioeconomy until 2050 and that are fit for use within hydrological catchment modelling, ecosystem service studies and stakeholder dialogue about possible changes in agricultural and forestry management practices.

Potential impacts of a future Nordic bioeconomy on surface water quality - Hannu Marttila; Ahti Lepistö; Anne Tolvanen; Marianne Bechmann; Katarina Kyllmar; Artti Juutinen; Hannah Wenng; Eva Skarbøvik; Martyn Futter; Pirkko Kortelainen; Katri Rankinen; Seppo Hellsten; et al. (Ambio, 2020)
Nordic water bodies face multiple stressors due to human activities, generating diffuse loading and climate change. The ‘green shift’ towards a bio-based economy poses new demands and increased pressure on the environment. Bioeconomy-related pressures consist primarily of more intensive land management to maximise production of biomass. These activities can add considerable nutrient and sediment loads to receiving waters, posing a threat to ecosystem services and good ecological status of surface waters. The potential threats of climate change and the ‘green shift’ highlight the need for improved understanding of catchment-scale water and element fluxes. Here, we assess possible bioeconomy-induced pressures on Nordic catchments and associated impacts on water quality. We suggest measures to protect water quality under the ‘green shift’ and propose ‘road maps’ towards sustainable catchment management. We also identify knowledge gaps and highlight the importance of long-term monitoring data and good models to evaluate changes in water quality, improve understanding of bioeconomy-related impacts, support mitigation measures and maintain ecosystem services.

Drivers of long‐term invertebrate community stability in changing Swedish lakes - Hannah B. Fried‐Petersen; Yimen G. Araya‐Ajoy; Martyn N. Futter; David G. Angeler (Global Change Biology, 2020)
Research on ecosystem stability has had a strong focus on local systems. However, environmental change often occurs slowly at broad spatial scales, which requires regional‐level assessments of long‐term stability. In this study, we assess the stability of macroinvertebrate communities across 105 lakes in the Swedish “lakescape.” Using a hierarchical mixed‐model approach, we first evaluate the environmental pressures affecting invertebrate communities in two ecoregions (north, south) using a 23 year time series (1995–2017) and then examine how a set of environmental and physical variables affect the stability of these communities. Results show that lake latitude, size, total phosphorus and alkalinity affect community composition in northern and southern lakes. We find that lake stability is affected by species richness and lake size in both ecoregions and alkalinity and total phosphorus in northern lakes. There is large heterogeneity in the patterns of community stability of individual lakes, but relationships between that stability and environmental drivers begin to emerge when the lakescape, composed of many discrete lakes, is the focal unit of study. The results of this study highlight that broad‐scale comparisons in combination with long time series are essential to understand the effects of environmental change on the stability of lake communities in space and time.

Statistical models for evaluating suspected artefacts in long-term environmental monitoring data - Claudia von Brömssen; Jens Fölster; Martyn Futter; Kerstin McEwan (Environmental Monitoring and Assessment, 2018)

Flows and sediment dynamics in the Ganga River under present and future climate scenarios - Sana Khan; Rajiv Sinha; Paul Whitehead; Sananda Sarkar; Li Jin; Martyn N. Futter (Hydrological Sciences Journal, 2018)

Towards an Improved Conceptualization of Riparian Zones in Boreal Forest Headwaters - José L. J. Ledesma; Martyn N. Futter; M. Blackburn; Fredrik Lidman; Thomas Grabs; Ryan A. Sponseller; Hjalmar Laudon; Kevin H. Bishop; Stephan J. Köhler (Ecosystems, 2018)

Nitrogen dynamics in managed boreal forests: Recent advances and future research directions - Ryan A. Sponseller; Michael J. Gundale; Martyn Futter; Eva Ring; Annika Nordin; Torgny Näsholm; Hjalmar Laudon (Ambio, 2016)

Conceptualizing and communicating management effects on forest water quality - Martyn N. Futter; Lars Högbom; Salar Valinia; Ryan A. Sponseller; Hjalmar Laudon (Ambio, 2016)

The role of biogeochemical hotspots, landscape heterogeneity, and hydrological connectivity for minimizing forestry effects on water quality - Hjalmar Laudon; Lenka Kuglerová; Ryan A. Sponseller; Martyn Futter; Annika Nordin; Kevin Bishop; Tomas Lundmark; Gustaf Egnell; Anneli M. Ågren (Ambio, 2016)

Evaluating common drivers for color, iron and organic carbon in Swedish watercourses - Johan Temnerud; Julia K. Hytteborn; Martyn N. Futter; Stephan J. Köhler (Ambio, 2014)

Long-term trends in water chemistry of acid-sensitive Swedish lakes show slow recovery from historic acidification - Martyn N. Futter; Salar Valinia; Stefan Löfgren; Stephan J. Köhler; Jens Fölster (Ambio, 2014)

The Swedish monitoring of surface waters: 50 years of adaptive monitoring - Jens Fölster; Richard K. Johnson; Martyn N. Futter; Anders Wilander (Ambio, 2014)

Assessing anthropogenic impact on boreal lakes with historical fish species distribution data and hydrogeochemical modeling - Salar Valinia; Göran Englund; Filip Moldan; Martyn N Futter; Stephan J Köhler; Kevin Bishop; Jens Fölster (Global Change Biology, 2014)
Quantifying the effects of human activity on the natural environment is dependent on credible estimates of reference conditions to define the state of the environment before the onset of adverse human impacts. In Europe, emission controls that aimed at restoring ecological status were based on hindcasts from process‐based models or paleolimnological reconstructions. For instance, 1860 is used in Europe as the target for restoration from acidification concerning biological and chemical parameters. A more practical problem is that the historical states of ecosystems and their function cannot be observed directly. Therefore, we (i) compare estimates of acidification based on long‐term observations of roach ( Rutilus rutilus ) populations with hindcast pH from the hydrogeochemical model MAGIC; (ii) discuss policy implications and possible scope for use of long‐term archival data for assessing human impacts on the natural environment and (iii) present a novel conceptual model for interpreting the importance of physico‐chemical and ecological deviations from reference conditions. Of the 85 lakes studied, 78 were coherently classified by both methods. In 1980, 28 lakes were classified as acidified with the MAGIC model, however, roach was present in 14 of these. In 2010, MAGIC predicted chemical recovery in 50% of the lakes, however roach only recolonized in five lakes after 1990, showing a lag between chemical and biological recovery. Our study is the first study of its kind to use long‐term archival biological data in concert with hydrogeochemical modeling for regional assessments of anthropogenic acidification. Based on our results, we show how the conceptual model can be used to understand and prioritize management of physico‐chemical and ecological effects of anthropogenic stressors on surface water quality.

Cross-scale ensemble projections of dissolved organic carbon dynamics in boreal forest streams - Stephen K. Oni; Martyn N. Futter; Claudia Teutschbein; Hjalmar Laudon (Climate Dynamics, 2014)

Almost 50 years of monitoring shows that climate, not forestry, controls long‐term organic carbon fluxes in a large boreal watershed - Ahti Lepistö; Martyn N Futter; Pirkko Kortelainen (Global Change Biology, 2014)
Here, we use a unique long‐term data set on total organic carbon ( TOC ) fluxes, its climatic drivers and effects of land management from a large boreal watershed in northern Finland. TOC and runoff have been monitored at several sites in the Simojoki watershed (3160 km 2 ) since the early 1960s. Annual TOC fluxes have increased significantly together with increased inter‐annual variability. Acid deposition in the area has been low and has not significantly influenced losses of TOC . Forest management, including ditching and clear felling, had a minor influence on TOC fluxes – seasonal and long‐term patterns in TOC were controlled primarily by changes in soil frost, seasonal precipitation, drought, and runoff. Deeper soil frost led to lower spring TOC concentrations in the river. Summer TOC concentrations were positively correlated with precipitation and soil moisture not temperature. There is some indication that drought conditions led to elevated TOC concentrations and fluxes in subsequent years (1998–2000). A sensitivity analysis of the INCA ‐C model results showed the importance of landscape position, land‐use type, and soil temperature as controls of modeled TOC concentrations. Model predictions were not sensitive to forest management. Our results are contradictory to some earlier plot‐scale and small catchment studies that have shown more profound forest management impacts on TOC fluxes. This shows the importance of scale when assessing the mechanisms controlling TOC fluxes and concentrations. The results highlight the value of long‐term multiple data sets to better understand ecosystem response to land management, climate change and extremes in northern ecosystems.

Is the Water Footprint an Appropriate Tool for Forestry and Forest Products: The Fennoscandian Case - Samuli Launiainen; Martyn N. Futter; David Ellison; Nicholas Clarke; Leena Finér; Lars Högbom; Ari Laurén; Eva Ring (Ambio, 2014)

Hydrology, forests and precipitation recycling: a reply to van der Ent et al - David Ellison; Martyn N. Futter; Kevin Bishop (Global Change Biology, 2012)

On the forest cover–water yield debate: from demand‐ to supply‐side thinking - David Ellison; Martyn N. Futter; Kevin Bishop (Global Change Biology, 2012)
Several major articles from the past decade and beyond conclude the impact of reforestation or afforestation on water yield is negative: additional forest cover will reduce and removing forests will raise downstream water availability. A second group of authors argue the opposite: planting additional forests should raise downstream water availability and intensify the hydrologic cycle. Obtaining supporting evidence for this second group of authors has been more difficult due to the larger scales at which the positive effects of forests on the water cycle may be seen. We argue that forest cover is inextricably linked to precipitation. Forest‐driven evapotranspiration removed from a particular catchment contributes to the availability of atmospheric moisture vapor and its cross‐continental transport, raising the likelihood of precipitation events and increasing water yield, in particular in continental interiors more distant from oceans. Seasonal relationships heighten the importance of this phenomenon. We review the arguments from different scales and perspectives. This clarifies the generally beneficial relationship between forest cover and the intensity of the hydrologic cycle. While evidence supports both sides of the argument – trees can reduce runoff at the small catchment scale – at larger scales, trees are more clearly linked to increased precipitation and water availability. Progressive deforestation, land conversion from forest to agriculture and urbanization have potentially negative consequences for global precipitation, prompting us to think of forest ecosystems as global public goods . Policy‐making attempts to measure product water footprints, estimate the value of ecosystem services, promote afforestation, develop drought mitigation strategies and otherwise manage land use must consider the linkage of forests to the supply of precipitation.

Riparian Zone Influence on Stream Water Dissolved Organic Carbon Concentrations at the Swedish Integrated Monitoring Sites - Mattias Winterdahl; Johan Temnerud; Martyn N. Futter; Stefan Löfgren; Filip Moldan; Kevin Bishop (Ambio, 2011)

Stream Nitrate Responds Rapidly to Decreasing Nitrate Deposition - Dolly N. Kothawala; Shaun A. Watmough; Martyn N. Futter; Leiming Zhang; Peter J. Dillon (Ecosystems, 2011)

Spatial analysis of ice phenology trends across the Laurentian Great Lakes region during a recent warming period - Olaf P. Jensen; Barbara J. Benson; John J. Magnuson; Virginia M. Card; Martyn N. Futter; Patricia A. Soranno; Kenton M. Stewart (Limnology and Oceanography, 2007)
We examined spatial patterns of trends in ice phenology and duration for 65 waterbodies across the Great Lakes region (Minnesota, Wisconsin, Michigan, Ontario, and New York) during a recent period of rapid climate warming (1975‐2004). Average rates of change in freeze (3.3 d decade −1 ) and breakup (22.1 d decade −1 ) dates were 5.8 and 3.3 times more rapid, respectively, than historical rates (1846‐1995) for Northern Hemisphere waterbodies. Average ice duration decreased by 5.3 d decade −1 . Over the same time period, average fall through spring temperatures in this region increased by 0.7°C decade −1 , while the average number of days with snow decreased by 5.0 d decade21, and the average snow depth on those days decreased by 1.7 cm decade −1 . Breakup date and ice duration trends varied over the study area, with faster changes occurring in the southwest. Trends for each site were compared to static waterbody characteristics and meteorological variables and their trends. The trend toward later freeze date was stronger in large, low‐elevation waterbodies; however, freeze date trends had no geographic patterns or relationships to meteorological variables. Variability in the strength of trends toward earlier breakup was partially explained by spatial differences in the rate of change in the number of days with snow cover, mean snow depth, air temperature (warmer locations showed stronger trends), and rate of change in air temperature. Differences in ice duration trends were explained best by a combination of elevation and the local rate of change in either temperature or the number of days with snow cover.

Patterns and Trends in Southern Ontario Lake ice Phenology - Martyn N. Futter (Environmental Monitoring and Assessment, 2003)

THE EFFECT OF EL NIÑO-RELATED DROUGHT ON THE RECOVERY OF ACIDIFIED LAKES - Peter J. Dillon; Lewis A. Molot; Martyn Futter (Environmental Monitoring and Assessment, 1997)